Maximizing Pv module’s power output through cooling by thermoelectric device - Mooko, Gauta Tshepo Valentine (Central University of Technology, 2023)
Solar energy, as the most abundant renewable resource, has seen a remarkable surge in utilization, predominantly through the adoption of solar photovoltaic panels. This adoption is driven by its eco-friendly nature and minimal environmental impact. Nonetheless, akin to any imperfect system, not all incident light photons are successfully converted into usable electrical energy. Instead, some solar energy remains unconverted, dissipating as heat across the surface of photovoltaic panels. This heat dissipation adversely affects the electrical efficiency of photovoltaic panels. Efficient cooling of the photovoltaic panel’s operational surface is crucial in the quest for higher efficiency in solar photovoltaic systems. Effective cooling not only substantially improves the electrical efficiency of photovoltaic modules however further mitigates cell degradation, thus extending the lifespan of these systems. The influence of temperature on the electrical efficiency of photovoltaic panels is particularly pronounced, when temperatures exceed 25°C. However, a gap in research has been identified in the development and application of optimizing control methods to reduce photovoltaic panel operating temperatures, without employing traditional cooling mediums. One promising approach, involves attaching a thermoelectric cooler to the rear of the photovoltaic panel, effectively reducing surface temperatures. To evaluate the economic viability of this approach, a comparative analysis will be conducted between the conventional reference system and the photovoltaic-thermoelectric cooler hybrid system. Therefore, in order to address the identified gap in research, a mathematical model describing the cooling process of photovoltaic modules was formulated and simulations were carried out. MATLAB was used and the optimization problem was solved, using the SCIP (Solving Constrained Integer Programs), in OPTI toolbox. The simulation outcomes, illustrate that precise control of the thermoelectric cooler has the potential to increase the electrical output power efficiency of photovoltaic modules by 9.27%, all while efficiently regulating the surface temperatures. Furthermore, the life cycle cost comparison, reveals that over the long term, the hybrid system may be more cost-effective, boasting a 10.56% cost saving over the 20-year project lifespan. A break-even point analysis indicated that the proposed system may break even in 6.5 years.
Master of Engineering in Electrical Engineering
Keywords: Photovoltaic; thermoelectric cooler; efficiency enhancement; temperature control; mathematical modelling; MATLAB SCIP simulation; economic feasibility.